NEW BIOSTRATIGRAPHIC DATA FROM THE LADINIAN PELAGIC LIMESTONES OF PIZZO DI SANT’OTIERO - MADONIE MOUNTAINS, SICILY. (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
New biostratigraphic data, based on conodont investigations, were collected from the Ladinian limestones recently described at Sant’Otiero, a locality near the Village of Petralia Sottana in the Madonie Mountains (Central-Northern Sicily). At this locality a new calcareous succession lying at the base of a major tectonic unit of the Maghrebian chain is described. This succession consists of a lower massive part formed by a carbonate megabreccia, the elements of which are shallow water extraclasts with dasycladalean algae (Diplopora annulatissima Pia), benthic foraminifers, “Tubiphytes” and problematic organisms commonly described from Anisian carbonate platforms. Upward a well-bedded succession of dark-gray Daonella -bearing calcilutites follows. The presence of the bivalve Daonella tyrolensis Mojsisovics in a Lumachella bed from the upper part of the calcilutites can be related to the ammonoid Protrachyceras longobardicum Zone, upper Ladinian in age (lower Longobardian). Upward a sharp contact(decollement?) with the typical sediments of the Mufara Formation can be observed. A re-sampling of the Daonella -bearing calcilutites for conodont investigation has been carried out in order to better constrain the age of this succession. The distribution of conodont species such as Budurovignathus  hungaricus (Kozur & Végh), B.  mungoensis (Diebel) and Paragondolella  trammeri (Kozur) among other conodonts, permits the correlation of the succession to the P. gradleri and P. archelaus ammonoid Zones, extending downwards the age of the calcilutites at Sant’Otiero to the upper Fassanian. This confirms that the Sant’Otiero succession is a key section to document Ladinian pelagic carbonate sedimentation in the westernmost termination of the Ionian Tethys.